(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The essay investigates the extent and the limits of “medicine beyond the cure”, from the point of view of constitutional law. Individual and collective prevention interventions, vaccination campaigns, health promotion through correct life-styles, palliative care, are just some examples of the expansive motion of medicine and its boundaries. On this ground, we find the problem of the balance between the individualistic dimension and the solidarity dimension in the protection of the right to health. In the concluding part, some critical points are highlighted regarding the spread of non-conventional medicines, which seem to project cure “beyond the medicine”.